Demand and unmet needs of contraception among sexually active in-union women in Nigeria: distribution, associated characteristics, barriers, and program implications (2018)
It is not clear whether the 16% unmet need for contraceptives in Nigeria indicates a success story. This study assessed the contraceptive prevalence rate (CPR), total contraceptive demand, and unmet needs and determined the distribution, determinants, and barriers to contraceptive demands and unmet needs in Nigeria. The fertility, breastfeeding, and contraceptive use information provided by 27,829 women who were either currently married or in a sexual union in the 2013 Nigeria Demographic and Health Survey (NDHS) were extracted. Associations between having unmet needs and the demographic, socioeconomic, and reproductive profiles of the respondents were assessed using bivariate and multiple logistic regression at 5% significance level. Multiple response data analysis techniques were used to assess barriers to nonuse of contraceptives. Data were weighted to reflect differentials in the population of in-union women in each geographical state. The modern CPR was 9.8% while total demand for contraception was 31.2%, consisting of unmet need at 16.1% and met needs at 15.1%. Unmet need for family planning was higher among rural women compared with urban women (16.8% vs. 14.9%); younger women (adjusted odds ratio [aOR] = 4.29; confidence interval [CI] = [3.03, 6.07]), women belonging to poorer economic status (aOR = 2.27, CI = [1.92, 2.68]), and women with no education (aOR = 3.23, CI = [2.60, 4.02]) had higher odds of unmet needs. The low unmet need should not be mistaken for a good progress in family planning programming in Nigeria; the success is better measured using the level of total demand for contraceptives and CPR. Interventions to improve the socioeconomic status of women, increase the knowledge of modern contraceptives, and improve women’s decision-making power should be prioritized.